2009
DOI: 10.1007/s00226-009-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopy, chemical and histochemical characterisation of wood and lignin of five tropical timber wood species of the family of Dipterocarpaceae

Abstract: The goal of this study was to characterise chemical and histochemical properties of five dipterocarp timber wood species (Dipterocarpus kerrii, Hopea plagata, Parashorea malaanoman, Shorea almon, and Shorea contorta) differing in wood service life and utilisation. Wood of H. plagata, the most durable species, contained the lowest concentrations of nitrogen and ligno-protein, the highest C/N ratio and the lowest lignin concentration per dry mass but the highest lignin and extractive concentrations per wood dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(105 citation statements)
references
References 34 publications
6
97
1
1
Order By: Relevance
“…Naumann et al (2005) demonstrated that FT-IR technology has an ability to identify wood fungi, and it is possible to detect fungi in wood by FT-IR microscopy. Rumana et al (2010) used FT-IR spectroscopy to characterize the lignin structure, and five tropical timber wood species of the family of Dipterocarpaceae were investigated with regard to chemical and histochemical properties. FT-IR spectroscopy, on the other hand, requires the preparation of small pellets with KBr which might be time consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%
“…Naumann et al (2005) demonstrated that FT-IR technology has an ability to identify wood fungi, and it is possible to detect fungi in wood by FT-IR microscopy. Rumana et al (2010) used FT-IR spectroscopy to characterize the lignin structure, and five tropical timber wood species of the family of Dipterocarpaceae were investigated with regard to chemical and histochemical properties. FT-IR spectroscopy, on the other hand, requires the preparation of small pellets with KBr which might be time consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%
“…In the 182 score plot from class dataset ( Fig. 2-B hemicelluloses (xylan/glucomannan) Bjarnestad and 206 Dahlman, 2002;207 Mohebby, 2008207 Mohebby, , 2005Rana et al, 2009;Stewart et al, 1995) . It seems that differences between groups can be 216 attributed to the lignin region.…”
Section: Sample Preparation 91mentioning
confidence: 99%
“…As mentioned before, C=O 239 stretching in lignin and carbohydrates seems relevant for the classification. The 240 greater contributor to the discrimination between subclass groups was the 241 wavenumber 1769, attributed in the literature to C=O stretching in acetyl groups 242 of hemicelluloses (xylan/glucomannan) Bjarnestad and 243 Dahlman, 2002;244 Mohebby, 2008244 Mohebby, , 2005Rana et al, 2009;Stewart et al, 1995), this contributor 245 was followed in order of importance (the second greatest F-value) by 1697 246 assigned to C=O stretching (Coates, 2000;Silverstein et al, 2005), 3613 and 3610 247 (O-H stretching (Coates, 2000)), and lastly 1701 related to Conj-CO-Conj lignin 248 Larkin, 2011). 249 STEPDISC method was run over different split datasets from ring dataset, the 250 imbalance effect on the results was also checked; in such a way, the discriminator 251 wavenumbers from the output of STEPDISC method were selected and used to 252 construct linear regression models.…”
Section: Sample Preparation 91mentioning
confidence: 99%
“…El hombro a 2900 cm -1 corresponde al grupo CH 2 guayacilosiringilo (Raiskila, 2007). La huella digital de cualquier espectro infrarrojo se analiza entre los 600 cm -1 y los 1800 cm -1 , los resultados obtenidos se compararon con los reportados por Rana, Langenfeld-Heyser, Finkeldey, y Polle (2010). Este autor realizó un estudio de IR de lignina proveniente de madera, aislada por diferentes métodos.…”
Section: Subproductos De La Deslignificaciónunclassified